2019
DOI: 10.5005/jp-journals-10015-1619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Penetration of Low Surface Tension Vehicles in Dentinal Tubules using Stereomicroscopy

Abstract: Aim:To evaluate and compare the dentinal tubule penetration of glycerine, propylene glycol and ringer's lactate solution. Materials and methods: Forty-five single-rooted human mandibular premolars with mature apices were decoronated keeping a length of 12 mm of a root. Biomechanical preparation till rotary protaper F2 and irrigation according to the protocol of all the roots was performed. The specimens were randomly assigned into three random groups (n = 15) of glycerine, propylene glycol and ringer lactate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Newer CSCs such as Biodentine and Bioceramic (BC) sealer, and MTA high plasticity (HP) can alter the radiopacifier agent into Ca tungstate or zirconium oxide. These constituents caused no alteration in color [26]. The second substitute is the addition of 5% zinc oxide (ZnO) to MTA as this ZnO converts bismuth oxide into bismite, a product that helps prevent the change of color [10].…”
Section: Color Stabilitymentioning
confidence: 99%
“…Newer CSCs such as Biodentine and Bioceramic (BC) sealer, and MTA high plasticity (HP) can alter the radiopacifier agent into Ca tungstate or zirconium oxide. These constituents caused no alteration in color [26]. The second substitute is the addition of 5% zinc oxide (ZnO) to MTA as this ZnO converts bismuth oxide into bismite, a product that helps prevent the change of color [10].…”
Section: Color Stabilitymentioning
confidence: 99%
“…A similar alcoholic surface-active agent is propylene glycol. Propylene glycol's ability to reduce surface tension has found application as a vehicle for better delivery of intracanal medicaments [10], and it has demonstrated better tissue dissolution and antimicrobial properties when combined with irrigants [11]. Previous studies have shown better wettability and penetration of 5% NaOCl with cetrimide and/or propylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Successful endodontic treatment is achieved by eliminating complete microbes from the root canal along with achieving a fluid tight seal by using materials of sufficient compatibility [1,2,3]. Although with the advent of latest techniques for endodontic treatment, with newer efficacious materials and instruments, the resolution of some cases [ 4] of periapical diseases is not achieved which necessitates surgical intervention [5].…”
Section: Introductionmentioning
confidence: 99%